Carta de Frederic W. Upham a Roberto H. Todd - Todd, Roberto H.; Upham, Frederic W. (My University, 1917)
Carta de presentación de John P. Hopkins
Keywords: Hopkins, John P.; Upham, Frederic W.--Correspondence.; Upham, Frederic W.--Correspondencia.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.